The effect of education on smoking behavior: new evidence from smoking durations of a sample of twins - Pierre Koning; Dinand Webbink; Nicholas G. Martin (Institute for the Study of Labor (IZA), 2010)
This paper analyses the effect of education on starting and quitting smoking, using longitudinal data of Australian twins. The endogeneity of education, censoring of smoking durations and the timing of starting smoking versus that of completion of education are taken into account by the flexible Mixed Proportional Hazard specification. Unobserved effects are assumed to be twin specific and possibly correlated with completed education years. We find that one additional year of education reduces the duration of smoking with 9 months but has no effect on the decision to start smoking.
Keywords: C41; I21; 330; Smoking; duration models; education; Bildungsniveau; Rauchen; Dauer; Australien